Autonomic function in Takotsubo syndrome long after the acute phase. (15th March 2017) - Lazzeroni, Davide; Bini, Matteo; Castiglioni, Paolo; Moderato, Luca; Ciraci', Chiara; Camaiora, Umberto; Ugolotti, Pietro Tito; Brambilla, Lorenzo; Brambilla, Valerio; Castrichini, Matteo; Ugo, Fabrizio; Gaibazzi, Nicola; et al.
Abstract: Objectives: Although it is well documented that an exaggerated sympathetic stimulation plays a role in the development of Takotsubo Syndrome (TS) during the acute phase, only few studies have focused on autonomic adaptations in stress-induced cardiomyopathy long after the acute phase. Aim of the study was to investigate whether an impairment of the autonomic function is still present long after a TS event. This was done by comparing the response to a maximal exercise test in TS patients after apparent recovery (> 1-year after the acute event) with that obtained in healthy subjects and in post-myocardial infarction (post-MI) patients. Methods: To assess heart rate recovery (HRR) and chronotropic response (CR), 24 TS patients, 25 healthy subjects and 22 post-MI patients underwent maximal exercise test, after at least 3 days of β-blockers wash-out. Results: HRR in TS patients (19.2 ± 9.7 bpm) was lower than in healthy subjects (27.7 ± 8.3, p = 0.003), and similar to post-MI patients (19.3 ± 8.4; p = 0.99). A decreasing CR trend (p=0.06), higher in healthy subjects (72±13%) than in TS (65±22%) and post-MI (57±21%) patients, was also found. Conclusion: Compared to healthy subjects, TS patients showed a blunted parasympathetic reactivation after exercise, similar to that observed in post-MI patients, thereby suggesting that vagal control of heart rate after exercise is abnormal long after the acute presentation of TS.